STRATEGI BISNIS LODGING DALAM MENINGKATKAN PENJUALAN DI DAERAH WISATA DI KABUPATEN LANGKAT - Syahrul, Syahrul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
This study aims to analyze the strategies used by lodging businesses in Langkat Regency, to increase sales through channel implementation. Employing a quantitative descriptive approach, the research focuses on several accommodation managers in the region. The research provides a detailed overview of how entrepreneurs and business managers in these sectors apply channel strategies to enhance sales, focusing on key elements such as awareness, evaluation, purchasing, delivery, and after-sales service. Data was collected through physical observation, literature review, interviews, and the distribution of questionnaires. The findings reveal that, in general, accommodation business managers in the study area have not yet fully optimized the implementation of the channel concept, with subvariables such as awareness, evaluation, purchasing, and after-sales service not being applied effectively. The delivery subvariable, however, is categorized as moderately implemented. Overall the lodging business operators have yet to fully optimize the channel strategies, with most variables still falling into the moderate category.